Semen quality and sperm ultrastructure of Himalayan snowtrout Schizothorax plagiostomus Heckel, 1838 - Bhatt, Gaurav; Singh, Shurveer; Bahugua, Vivek; Chowdhary, Ashish K.; Bhardwaj, Siddhand; Bahuguna, S. N. (Indian Journal of Fisheries, 2017)
The aim of this study was to characterise physical and biochemical aspects of semen as well as to investigate the fine structure of spermatozoa of the Himalayan snowtrout Schizothorax plagiostomus Heckel, 1838 using scanning and transmission electron microscopy. The species breed twice in a year and semen was collected during both seasons, i.e. from 24 males in February and March, 2015 and from 30 males in September and October, 2015. Size of the fish ranged from 13.5 to 36 cm in February-March and 12.3 to 38 cm in September-October. The mean milt volume (ml), sperm density (×1010 ml-1) and spermatocrit (%) values were 2.25±1.26, 2.22±0.53 and 78.87± 8.25 in February-March and 2.12±1.25, 2.12±0.52 and 75.54±8.23 in September-October respectively. Biochemical parameters of seminal plasma viz., total protein (g dl-1), carbohydrates (mg dl-1) and total lipids were 0.312±0.05, 1.348±0.07 and 26.4±2.23 in February-March and 0.340±0.05, 1.34±0.1 and 26.4±3.19 in September-October respectively. Scanning and transmission electron microscopy studies of sperm revealed that the sperm was composed of an ovoid shaped head without acrosome, ellipsoidal midpiece with mitochondria and tail or flagellum. Flagellum had a typical 9+2 axoneme arrangement. The mean length (μm) of head, midpiece, flagella and total length of sperm were 1.82±0.24, 0.35±0.07, 20.18±0.79 and 22.3±3 respectively. For both the breeding seasons, sperm motility decreased significantly with time post-activation.